Assessment of Some Genetic thrombophilias in Nigerian patients with Venous Thromboembolism (Nigerian Journal of Physiological Sciences, 2025)
Venous thromboembolism (VTE) is a leading cause of mortality globally, resulting from genetic risk factors and/or acquired risk factors like oral contraceptives, smoking, diabetes, immobilization, cancer, trauma, fracture, and surgical procedures. This study aims to assess the involvement and prevalence of some genetic thrombophilias in Nigerian VTE patients. A total of 107 participants were recruited, comprising 67 individuals with VTE from three tertiary hospitals in Southwest Nigeria and 50 apparently healthy controls. Parameters included the absolute platelet count, prothrombin time (PT), activated partial thromboplastin time (APTT), D-dimer, protein C, protein S, and antithrombin levels. The VTE patients had significantly lower mean platelet counts, protein C and S antigenic concentrations, and protein S activity (p